Peningkatan Kapasitas dan Akses Pasar melalui Program Pelatihan dan Pendampingan UMKM Bakpao Barokah - Estika Al Bayentika; Yovie Aditya Ainur Khalim; Ainun Fitri Amelia; Lana Ihda Rahmatika; Juliandheo Putra Prasetya; Amnan Haris (Jurnal Dharma Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, but many MSME business owners still face obstacles in marketing and business management. One MSME in Sangkanjoyo Village, Bakpao Barokah, has products that are popular with the community but still relies on conventional promotion, limiting its market reach. This community service activity aims to increase business capacity through the use of logos, the creation of packaging stickers, and digitalization assistance with Google Maps Business and Shopee Food. The method used is Participatory Action Research (PAR), with the following stages: planning, implementation, monitoring, and evaluation. The results of the activity show that the Bakpao Barokah owner has succeeded in utilizing digital media for promotion, understanding online business account management, and strengthening product identity through packaging. This community service activity has a positive impact, including increased understanding of digital marketing, expanded market access, and a more professional business image